2008
DOI: 10.1111/j.1747-0080.2007.00175.x
|View full text |Cite
|
Sign up to set email alerts
|

Still there's no food! Food insecurity in a refugee population in Perth, Western Australia

Abstract: Aim:  To identify food insecurity and examine its association with socio‐demographic factors in a group of newly arrived refugees. Methods:  Structured questionnaire based around the same question asked during the National Nutrition Survey (1995). The questionnaire was administered to a service‐based sample of clients accessing early intervention services. Fifty‐one individuals who were newly arrived refugees, resident in Australia for less than 12 months and who were receiving torture and trauma counselling. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
127
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(137 citation statements)
references
References 12 publications
(23 reference statements)
7
127
3
Order By: Relevance
“…Policy recommendations include: i) incorporating goals and strategies to improve child FS into public health plans or develop stand-alone FS policies; 26,[50][51][52] ii) ensuring that government welfare policies act as both adequate 'safety nets' and 'springboards' out of disadvantage; 4 and iii) supporting the establishment of local employment opportunities in regional and remote areas, to increase financial security among families, particular, equitable access to affordable, nutritious food options for vulnerable groups that are FI should be a priority. 4,12,14,23,26,51,53,54 Recommendations for future research include: i) further investigation and monitoring of FI and its determinants in Australia from multiple perspectives, 8,43,46,56 especially among children, regional and remote residents; 52 and ii) longitudinal research to investigate the impact of FI on children's behaviours and resulting health outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Policy recommendations include: i) incorporating goals and strategies to improve child FS into public health plans or develop stand-alone FS policies; 26,[50][51][52] ii) ensuring that government welfare policies act as both adequate 'safety nets' and 'springboards' out of disadvantage; 4 and iii) supporting the establishment of local employment opportunities in regional and remote areas, to increase financial security among families, particular, equitable access to affordable, nutritious food options for vulnerable groups that are FI should be a priority. 4,12,14,23,26,51,53,54 Recommendations for future research include: i) further investigation and monitoring of FI and its determinants in Australia from multiple perspectives, 8,43,46,56 especially among children, regional and remote residents; 52 and ii) longitudinal research to investigate the impact of FI on children's behaviours and resulting health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…13 As a nation, Australia lags behind in the accurate measurement of FI among its population, especially children. Previous FI studies in Australia 8,[14][15][16] measured FI using a single question, or a few broad questions, which may not adequately establish the extent of the issue. Furthermore, previous Australian studies measured FI among adults and child residents, but as reported by adults, and by and large on the urban population.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Data collected in South Australia estimates the food insecurity rate to be approximately 7% [22]. However, this increases among at-risk groups including: unemployed (11.3%), rental households (15.8%) [23], those identifying as Aboriginal or Torres Strait Islander (23%) [24] and recently arrived refugees (71%) [25].…”
Section: Consideration Of Food Costs As a Fppmentioning
confidence: 99%
“…However, while there are studies in both representative samples and high-risk populations of food access limited by economic resources (15)(16)(17)(18)(19) , there has been limited research examining physical constraints to food access, although these additional factors have been hypothesised to restrict to access and impact on food intake particularly in the elderly (10) . Previous research, reviewed by White (20) , highlighted the role of car access in the choice of food outlets.…”
mentioning
confidence: 99%